2018
DOI: 10.3168/jds.2017-14278
|View full text |Cite
|
Sign up to set email alerts
|

Methane production, rumen fermentation, and diet digestibility of Holstein and Jersey dairy cows being divergent in residual feed intake and fed at 2 forage-to-concentrate ratios

Abstract: Improving feed efficiency of dairy cows through breeding is expected to reduce enteric methane production per unit of milk produced. This study examined the effect of 2 forage-to-concentrate ratios on methane production, rumen fermentation, and nutrient digestibility in Holstein and Jersey dairy cows divergent in residual feed intake (RFI). Before experimental onset, RFI was estimated using a random regression model on phenotypic herd data. Ten lactating Holstein and 10 lactating Jersey cows were extracted fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
62
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(81 citation statements)
references
References 44 publications
(68 reference statements)
15
62
1
3
Order By: Relevance
“…The components of MSEP were 0.62 for error-of-central-tendency, 0.20 for error-due-to-regression, and 8.1 for error-of-disturbance. Similar results were obtained for Equations (3) and 7 4, and (c) Equation 7showing the observed methane yield against equation-predicted methane yield, for 32 individual [6], (open circles) and 67 treatment means from 16 previously published experiments [14,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] (closed circles) with 1:1 line of agreement (dashed).…”
Section: Equation Numbersupporting
confidence: 80%
See 1 more Smart Citation
“…The components of MSEP were 0.62 for error-of-central-tendency, 0.20 for error-due-to-regression, and 8.1 for error-of-disturbance. Similar results were obtained for Equations (3) and 7 4, and (c) Equation 7showing the observed methane yield against equation-predicted methane yield, for 32 individual [6], (open circles) and 67 treatment means from 16 previously published experiments [14,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] (closed circles) with 1:1 line of agreement (dashed).…”
Section: Equation Numbersupporting
confidence: 80%
“…Subsequent work by Smith et al [60], in which ruminal fluid was sampled 3 h after the start of feeding, reported a weak negative correlation between methane yield and individual VFA proportions. 4, and (c) Equation 7showing the observed methane yield against equation-predicted methane yield, for 32 individual [6], (open circles) and 67 treatment means from 16 previously published experiments [14,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] (closed circles) with 1:1 line of agreement (dashed).…”
Section: Discussionmentioning
confidence: 96%
“…In the review of Richardson and Herd [41], digestibility was assumed to account for 10% of the variation in RFI on average in beef cattle, while Lovendahl et al [42], in their review of dairy cattle, concluded that between-cow variation in digestibility alone was too small to explain the observed variation in feed efficiency. Nonetheless, higher digestibility of DM or NDF was found in low-RFI as compared to high-RFI cattle in the studies of McDonnell et al [15] and Oliveira et al [17] with beef cattle and Olijhoek et al [43] with dairy Holstein cows. On the other hand, no significant difference was observed in the studies of Nkrumah et al [7], Fitzsimons et al [12] and Fitzsimons et al [44] with beef cattle and Olijhoek et al [43] with dairy Jersey cows and Fischer et al [45] with dairy Holstein cows.…”
Section: Calculated Growth and Methane Efficiency Traitsmentioning
confidence: 89%
“…Nonetheless, higher digestibility of DM or NDF was found in low-RFI as compared to high-RFI cattle in the studies of McDonnell et al [15] and Oliveira et al [17] with beef cattle and Olijhoek et al [43] with dairy Holstein cows. On the other hand, no significant difference was observed in the studies of Nkrumah et al [7], Fitzsimons et al [12] and Fitzsimons et al [44] with beef cattle and Olijhoek et al [43] with dairy Jersey cows and Fischer et al [45] with dairy Holstein cows. Interestingly, a higher digestibility and a higher methane yield were observed in low-RFI beef heifers tested with three different diets by McDonnell et al [15] and in low-RFI beef Nellore tested in feedlot by Oliveira et al [17].…”
Section: Calculated Growth and Methane Efficiency Traitsmentioning
confidence: 89%
“…As for the branched-chain fatty acids, the iso-fatty acids are produced from isobutyrate and isovalerate while antiso-fatty acids are originated from 2-methybutyrate in ruminants, as summarized by Vlaeminck et al [11]. The generation of these short chain fatty acids is not only in uenced by dietary strategy [3,26], but also highly depending on ruminal environment and physiological conditions of cows [27]. Indeed, studies regarding ruminal OBCFA productions in cows fed rations with different ratios of forage and concentrate have shown contrasting results.…”
Section: Discussionmentioning
confidence: 99%